Досвід Великої Британії у програмно-методичному забезпеченні дистанційної підготовки майбутніх учителів іноземної мови - Гарбуза, Тетяна (Studies in Comparative Education, 2013)
У статті розглянуто програмно-методичне забезпечення професійної підготовки вчителів іноземної мови, його основні складники й особливості в системі дистанційного навчання університетів Великої Британії. Актуальність теми зумовлена державною освітньою політикою України, що передбачає істотні зміни в підготовці педагогічних кадрів, у тому числі вчителів іноземної мови, з огляду на загальнонаціональні інтереси і провідні тенденції розвитку світового освітнього простору. В статье рассмотрено программно-методическое обеспечение профессиональной подготовки учителей иностранного языка, его основные составляющие и особенности в системе дистанционного обучения университетов Великобритании. Актуальность темы обусловлена государственной образовательной политикой Украины, предусматривающей существенные изменения в подготовке педагогических кадров, в том числе учителей иностранного языка, учитывая общенациональные интересы и ведущие тенденции развития мирового образовательного пространства. Actuality of the theme is caused by the state educational policy of Ukraine, which provides for significant changes in the teachers training, including foreign language teachers, taking into account the national interests of society and the main trends of world education development. The article describes the program methodical support for the foreign language teachers training, its main components and features in the system of distance education of Great Britain universities. The program-methodical support is regarded as the totality of educational content, legal base, teaching materials, methodologies, tutorials (individual, group), teleconferences, webinars, thematic forums, which are implemented through software, organizational and other didactic resources (Internet, telephone networks and electronic information carriers and others) providing a set of high-quality educational services. In the article it is proved that feature of foreign language teacher training at a distance in the UK is a methodology of distance learning. It is implemented through a set of interrelated pedagogical and information and communication technologies. Pedagogical technologies include technology of self-educational activity, credit-modular and project technologies. Information and communication technologies of training are realized through the creation, accumulation, storage and access to web-resources (electronic resources) within the curriculum (subjects), as well as through ensuring the organisation and support of educational process using specialized software and telecommunication facilities, including the Internet. In the article it is indicated that the ICT application in distance education is impossible without the use of the appropriate learning tools. The information and communication learning tools include: the telephone network, the Internet, electronic means of communication, means of on-line interaction between the subjects of education, multimedia, electronic media, electronic textbooks.